Influence of calcination temperature on anatase to rutile phase transformation in TiO2nanoparticles synthesized by the modified sol-gel method - Natda Wetchakun (2018)
Titanium dioxide (TiO2) nanoparticles with different ratios of anatase to rutile transformation were synthesized by the modified sol-gel method. The optical properties were investigated by UV-vis diffuse reflectance spectrophotometry. Phase transformation, crystallinity, and crystal structure of the calcined TiO2samples were derived from X-ray diffraction analysis. The morphology and particle size of TiO2were characterized by transmission electron microscopy (TEM). The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on TiO2samples. TiO2nanoparticles calcined at 400 °C for 3 h possessed the highest specific surface area of 97 m2g- 1. The temperature of anatase to rutile transformation was found between 500 and 600 °C, and then completely transformed to rutile phase at 600 °C. Average particle sizes of the nanoparticles were in the range of 10-50 nm at calcination temperature between 400 and 600 °C. At higher temperature clearly favored particles growth and agglomerates are corresponded to decrease specific surface area. © 2012 Published by Elsevier B.V. All rights reserved.